Model Kepemimpinan Ulama Perempuan dalam Mengelola Pendidikan Pesantren di Lampung - Dwi Noviatul Zahra; Tri Mulyanto (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research aims to explore the leadership model of female ulama in managing Islamic boarding school education in Lampung and analyze strategies for adapting Islamic boarding school education to modernity without abandoning the Islamic boarding school's identity. This research uses a descriptive qualitative approach with the type of field research. Data was collected through observations of a series of educational activities in Islamic boarding schools, in-depth interviews with female clerics, Islamic boarding school administrators, and Islamic boarding school students, then documentation at five Islamic boarding schools managed by female clerics in Lampung, namely the Tri Bhakti At-Taqwa Islamic Boarding School, East Lampung, Al-Hikmah Bandar Lampung, Darussa'adah Central Lampung, Roudlotus Sholihin West Lampung, and Istiqomah Al-Amin South Lampung. Data analysis was carried out through stages of data reduction, data presentation, and continuous conclusion drawing. The research results show that the leadership of female ulama in Lampung Islamic boarding schools displays a variety of dynamic models, especially in human resource (HR) management and curriculum development. There are two main models in HR management, namely the empowerment model for senior students and the selection-based professionalization model. In the curriculum aspect, the five Islamic boarding schools integrate Salaf traditions with modern formal education in different proportions, giving rise to their respective institutional differences. Several Islamic boarding schools have developed superior programs such as express learning programs, tahfiz Al-Qur'an, Islamic entrepreneurship, and religious congregation education as a form of response to community needs. Apart from that, adaptation to technology and modernization are important characteristics of female ulama leadership in the contemporary era. Islamic boarding schools optimize the use of online learning platforms, digitalization of books, social media and marketplaces to strengthen education and economic independence. The findings of this research confirm that the leadership of female ulama in Lampung Islamic boarding schools is transformative and adaptive, able to negotiate between tradition and modernity, and contribute significantly to strengthening inclusive, responsive and sustainable Islamic education.